High ratio of C-reactive protein to albumin is associated with hemorrhagic transformation and poor functional outcomes in acute ischemic stroke patients after thrombolysis - Xu, Tong; Xia, Lingfan; Wu, Yucong; Xu, Ye; Xu, Xuan; Zhang, Wangyu; Zhou, Congcong; Fu, Fangwang; Cao, Yungang; Han, Zhao (Frontiers in Aging Neuroscience, 2023)
Background In patients with acute ischemic stroke, hemorrhagic transformation (HT) is a common complication after intravenous thrombolysis (IVT). In this study, we evaluated the relationship between the ratio of C-reactive protein to albumin (CAR) before thrombolysis, HT, and functional outcomes in patients with acute ischemic stroke. Methods We retrospectively analyzed data from 354 patients who received thrombolytic therapy at the Second Affiliated Hospital of the Wenzhou Medical University in China between July 2014 and May 2022. CAR was measured on admission, and HT was identified by cranial computed tomography (CT) within 24–36 h after treatment. Poor outcome was defined as a score on the modified Rankin Scale (mRS) > 2 at discharge. The multivariate logistic regression model was used to investigate the association between CAR, HT, and poor outcome after thrombolysis, respectively. Results A total of 354 patients were analyzed, and their median CAR was 0.61 (interquartile range, 0.24–1.28). CAR was significantly higher in the 56 patients (15.8%) who experienced HT than in those who did not (0.94 vs. 0.56, p < 0.001), and the 131 patients (37.0%) who experienced poor outcome than in those who did not (0.87 vs. 0.43, p < 0.001). Multivariate logistic regression indicated that CAR was an independent risk factor for both HT and poor outcome. The risk of HT was significantly higher among patients whose CAR fell in the fourth quartile than among those with CAR in the first quartile (OR 6.64, 95% CI 1.83 to 24.17, p = 0.004). Patients with CAR in the third quartile were more likely to experience poor outcome (OR 3.35, 95% CI 1.32 to 8.51, p = 0.01), as were those in the fourth quartile (OR 7.33, 95% CI 2.62 to 20.50, p < 0.001), compared to patients with CAR in the first quartile. Conclusion High ratio of C-reactive protein to albumin in individuals with ischemic stroke is associated with an increased risk of HT and poor functional outcomes after thrombolysis.